Структурні механізми взаємодії дефосфорильованих 2`-5`-триаденілатів з білком S100A1 - Скоробогатов, О.Ю.; Жуков, І.Ю.; Ткачук, З.Ю. (Доповіді НАН України, 2020)
За допомогою методів ЯМР спектроскопії та комп'ютерного моделювання вивчали структурні механізми
взаємодії дефосфорильованих 2´5´
триаденілатів з білком S100A1. Встановлено, що дефосфорильований 2´5´
триаденілат зв'язується з білком S100A1 на межі Са²⁺
зв'язувального домену та лінкерного регіо ну.
Утворення комплексу білок—триаденілат стабілізується трьома зв'язками, два з яких електростатичні,
а один водневий. Зафіксовані особливості взаємодії дефосфорильованого 2´5´
триаденілату з S100A1 можуть бути підґрунтям для пояснення однієї з неописаних раніше функцій дефосфорильованого 2´5´
триаденілату. We study the structural mechanisms of interaction of dephosphorylated 2´5´ triadenylates
with S100A1 protein
by NMR spectroscopy and computer simulation methods. Earlier, it was demonstrated that 2´5´ triadenylates
are capable of stimulating the muscle contraction via a direct or indirect interaction with the Ryano dine
receptor (RyR). One of the key regulators of this intracellular Са²⁺ pump is a calciumbinding
protein S100A1.
We assumed that the naturally occurring 2´5´ triadenylate
may interact with S100A1 directly, by exhibiting its
effect, and took a detailed look at the interaction. It is shown that dephosphorylated 2´5´ triadenylate
binds to
S100A1 within the Са²⁺ binding
loop/linker interface, where the aminoacids within the S100A1 homodimer
displayed the highest amplitude of chemical shifts. Complex formation turned out to be stabilized by the formation
of two electrostatic and one hydrogen bonds. The data obtained may suggest an insight into how the
naturally occurring 2´5´ triadenylate
exhibits its purely biological function. An alternative possible scenario is
the interaction between 2´5´ triadenylate
and CAM kinase, which leads to the alteration of the latter’s functioning,
which further affects the RyR. S100A1’s antagonist regarding the RyR functioning, Calmodulin, was
earlier shown to interact with 2´5´ triadenylate,
which led to the Са²⁺ affinity alteration of the latter. Collectively,
these data assume that 2´5´ triadenylate interacts with both major regulators of RyR’s Са²⁺releasing activity. С помощью методов ЯМР спектроскопии и компьютерного моделирования изучали структурные меха
низмы взаимодействия дефосфорилированного 2´5´
триаденилата с белком S100A1. Установлено, что дефосфорилированный 2´5´
триаденилат связывается с белком S100A1 на грани Са²⁺
связывающего домена и линкерного региона. Образование комплекса белок—триаденилат стабилизируется тремя связями,
два из которых электростатические, а один — водородный. Зафиксированные особенности взаимодействия дефосфорилированного 2´5´
триаденилата с S100A1 могут служить в качестве основы для объясне
ния одной из неописанных ранее функций дефосфорилированного 2´5´
триаденилата.